(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The construction buildings which are present in and around coastal area are severely facing lot of problems. This is due to penetration of sea salts. This leads to damage of structure fast. The average NACL Concentration of sea water is about3.5%. In this study , Marble Dust powder as been taken to analyze the chemical and physical properties of the concrete which is partial replaced with marble dust powder as fine aggregate by 10%,20%,30%,40% and 50%by weight of fine Aggregate. After replacing this marble dust powder as fine aggregate, cylinders and cubes are casted. After casting this cubes and cylinders, they are using to know its both compressive as well as tensile strength by using compression test and split tensile strength for 7 days and 28 days.